Catastrophic health expenditure of Vietnamese patients with gallstone diseases – a case for health insurance policy revaluation - Tran BX; Tran TD; Nathan N; Ngo CQ; Nguyen LT; Nguyen LH; Nguyen HLT; Nguyen CT; Do HP; Nguyen THT; Tran TT; Thai TPT; et al. (Dove Medical Press, 2019)
Bach Xuan Tran,1,2,* Tho Dinh Tran,3,* Nila Nathan,4 Chau Quy Ngo,5 Loi Thi Nguyen,6 Long Hoang Nguyen,7 Huong Lan Thi Nguyen,8 Cuong Tat Nguyen,8 Huyen Phuc Do,7 Trang Huyen Thi Nguyen,9 Tung Thanh Tran,9 Thao Phuong Thi Thai,10,11 Anh Kim Dang,8 Nam Ba Nguyen,7 Carl A Latkin,2 Cyrus SH Ho,12 Roger CM Ho7,13 1Department of Health Economics, Institute for Preventive Medicine and Public Health, Hanoi Medical University, Hanoi, Vietnam; 2Department of Health, Behavior and Society, Bloomberg School of Public Health, Johns Hopkins University, Baltimore, MD, USA; 3Department of Hepatobiliary Surgery, Vietnam-Germany Hospital, Hanoi, Vietnam; 4University of California, Santa Barbara, Santa Barbara, CA, USA; 5Department of Internal Medicine, Hanoi Medical University, Hanoi, Vietnam; 6Woolcock Institute of Medical Research Vietnam, Hanoi, Vietnam; 7Center of Excellence in Behavioral Medicine, Nguyen Tat Thanh University, Ho Chi Minh City, Vietnam; 8Institute for Global Health Innovations, Duy Tan University, Danang, Vietnam; 9Center of Excellence in Evidence-based Medicine, Nguyen Tat Thanh University, Ho Chi Minh City, Vietnam; 10Department of General Planning, Friendship Hospital, Hanoi, Vietnam; 11Department of Cardiology, Friendship Hospital, Hanoi, Vietnam; 12Department of Psychological Medicine, National University Hospital, Singapore; 13Department of Psychological Medicine, Yong Loo Lin School of Medicine, National University of Singapore, Singapore *These authors contributed equally to this work Purpose: Despite gallstone diseases (GSDs) being a major public health concern with both acute and chronic episodes, none of the studies in Vietnam has been conducted to investigate the household expenditure for the GSD treatment. The objective of this study was to estimate the costs of managing GSD and to explore the prevalence and determinants of catastrophic health expenditure (CHE) among Vietnamese patients.Materials and methods: A cross-sectional study was conducted from June 2016 to March 2017 in the Department of Hepatobiliary and Pancreatic Surgery, Viet Duc Hospital in Hanoi, Vietnam. A total of 206 patients were enrolled. Demographic and socioeconomic data, household income, and direct and indirect medical costs of patients seeking treatment for GSD were collected through face-to-face interview. Multivariate logistic regression was used to explore factors associated with CHE.Results: The prevalence of CHE in patients suffering from GSD was 35%. The percentage of patients who were covered by health insurance and at risk for CHE was 41.2%, significantly higher than that of those noninsured (15.8%). Proportions of patients with and without health insurance who sought outpatient treatment were 30.6% and 81.6%, respectively. Patients who were divorced or widowed and had intrahepatic gallstones were significantly more likely to experience CHE. Those who were outpatients, were women, had history of pharmacological treatment to parasitic infection, and belong to middle and highest monthly household income quantile were significantly less likely to experience CHE.Conclusion: The findings suggested that efforts to re-evaluate health insurance reimbursement capacity, especially for acute diseases and taking into account the varying preferences of people with different disease severity, should be conducted by health authority. Further studies concerning CHE of GSD in the context of ongoing health policy reform should consider utilizing WHO-recommended measures like the fairness in financial contribution index, as well as taking into consideration the behavioral aspects of health care spending. Keywords: catastrophic health expenditure, gallstone, health insurance, out-of-pocket payments, Vietnam